2005
DOI: 10.1007/s00213-005-0108-2
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral effects of systemically administered MK-212 are prevented by ritanserin microinfusion into the basolateral amygdala of rats exposed to the elevated plus-maze

Abstract: MK-212 increases anxiety and decreases locomotor activity. The anxiogenic-like profile of 5-HT2 receptor activation is prevented by the blockade of 5-HT2 receptors within the BLA, which does not have an effect by itself upon basal anxiety levels triggered by the EPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 83 publications
(119 reference statements)
0
30
1
2
Order By: Relevance
“…For example, hypoactivity in the elevated plus maze can overcome the detection of anxiogenic-like effects in some experimental manipulations [60] but not in others [61]. Moreover, a motor effect in the elevated plus maze can be part of the defense response to an anxiogenic compound [62].…”
Section: Problem Of Locomotor Activitymentioning
confidence: 99%
“…For example, hypoactivity in the elevated plus maze can overcome the detection of anxiogenic-like effects in some experimental manipulations [60] but not in others [61]. Moreover, a motor effect in the elevated plus maze can be part of the defense response to an anxiogenic compound [62].…”
Section: Problem Of Locomotor Activitymentioning
confidence: 99%
“…For example, with regards the association between the amygdala and the fear responses, it has been reported that the basolateral but not the core center of amygdala is associated with fear responses induced by microinjection of HTR2C selective agonists (SB-242084, MK-212) in those brain areas in rats [Campbell and Merchant, 2003;de Mello Cruz et al, 2005]. Intriguingly, when a less specific agonist was administered (mCPP), a fear response was elicited as well, but mCPP triggered a latency to investigate new objects that was not associated with SB-242084 administration, suggesting that HTR2C plays a specific role in a fear reaction that does not dampen the explorative behavior.…”
Section: Htr2c Agonist-antagonist Challengesmentioning
confidence: 99%
“…Animal studies also suggest that serotonergic neurotransmission in the basolateral nuclear complex of the amygdala (BLC) plays a critical role in stress, anxiety, and depression, but the exact effects depend on the type of serotonin receptor activated (Zangrossi and Graeff, 1994;Graeff et al, 1996;Zangrossi et al, 1999;De Mello Cruz et al, 2005;Abrams et al, 2005;Inoue et al, 2004). The type 3 serotonin receptor (5-HT 3 R) is unique in that it is the only serotonin receptor that is a ligand-gated ion channel (Barns and Sharp, 1999;Chameau and van Hooft, 2006).…”
Section: Nih Public Accessmentioning
confidence: 99%